Effectiveness of Selective Laser Trabeculoplasty Applied to 360° vs. 180° of the Angle - Abraham Nirappel; Emma Klug; Rebecca Ye; Nathan Hall; Marika Chachanidze; Ta C. Chang; David Solá-Del Valle (Journal of Ophthalmology)
Purpose. To compare the effectiveness and safety of 360° and 180° of Selective Laser Trabeculoplasty (SLT) for the treatment of elevated intraocular pressure (IOP). Methods. Retrospective cohort study. The main outcome measure was the Kaplan–Meier analysis comparing the cumulative probabilities of survival between the 360° and 180° SLT groups in terms of IOP reduction. Success was defined as ≥20% IOP reduction from baseline with an IOP between 5–18 mmHg and ≤1 glaucoma medication added postoperatively. Additional outcome measures included changes in average IOP, number of glaucoma medications, and the incidence of postoperative IOP spikes. Measurements were obtained at 6 weeks, 1 year, and 2 years postoperatively. Results. Two hundred and fifty-eight eyes of 258 patients were included in the 360° group, and 196 eyes of 196 patients were included in the 180° group. The mean IOP reductions at 2 years were 2.21 ± 2.02 mmHg and 2.43 ± 1.81 mmHg (p=0.33) in the 180° and 360° groups, respectively. There were no significant differences in the incidence of postoperative IOP spikes between the two groups. There was a significant difference in the survival curves of the two groups (p=0.035). The Cox proportional-hazard model indicated that 360° of SLT application was a significant predictor of long-term success (p=0.030). Conclusions. 360° of SLT application seems to provide for greater long-term IOP control than 180° of application without putting patients at an elevated risk for postoperative IOP spikes.